Understanding The Relationships between Service Quality, Customer Satisfaction and Loyalty: An Investigation of Ghana’s Retail Banking Sector - Kasser Tee, Daniel; Preko; Evans Tee, Alex (British Journal of Marketing Studies, 2018)
This study set out to examine the interrelationships between service quality, customer satisfaction, and customer loyalty for the Ghana banking industry. The paper also evaluates the effects of the individual dimensions of service quality on overall service quality. Primary research data were collected using questionnaires administered face-to-face, via systematic random sampling approach. Confirmatory Factor Analyses (CFA) was then used to test the hypotheses and address the research objectives as well. The results showed that the three variables were positively interrelated, albeit with different p-values for significance. The five dimensions of service quality, tangibility, reliability, responsiveness, assurance and empathy, each affects overall service quality positively and significantly). The effects of service quality on customer satisfaction was direct, positive but insignificant. In the same manner, customer satisfaction positively but insignificantly impacts customer loyalty. Service quality was seen to positively and significantly affect customer loyalty in this study. The findings therefore serve as a good guide for banks to work at improving service quality, which will in turn positively influence satisfaction and loyalty.